RANKED KEY FACTOR THAT AFFECT PERSON DECISION TRANSFORMING TO AN ELECTRIC VEHICLE : STRUCTURAL EQUATION MODELLING - Juliano, Ade; Cahyo, Winda Nur (Journal of Industrial Engineering Management, 2023)
The development of electric vehicles (EVs) has significantly disrupted the world's road transportation industry. EVs are predicted to account for more than 50% of new vehicle sales globally by 2035, however demand will differ greatly from country to country. Automobile is one of Indonesia’s key industry that support GDP, it is important for the industry to adapt to the transformation from ICE (Internal Combustion Engine) to EV (Electric Vehicle). Using the SEM (Structural Equation Model) Analysis approach, this research will help the automobile industry in Indonesia by reviewing and analyzing the key factor of Electric Vehicles. From this analysis, the industry can learn and implement the right strategy to penetrate the potential EV demand of Indonesia market.